Frailty and outcomes of vascular access for hemodialysis – a scoping review - Dias, Lara R. (2025)
INTRODUCTION: Frailty is an age-related condition related to the decline of physiologic capacity and the increased vulnerability to stressors. It is associated with increased mortality, hospitalizations, and healthcare costs. Dialysis patients, due to age and comorbidities, are especially vulnerable to frailty. The aim of this review was to assess the impact of frailty on outcomes of vascular access for haemodialysis. METHODS: A search was conducted on PubMed, Scopus and Cochrane to identify articles reporting on frailty and outcomes of vascular access in dialysis patients. RESULTS: A total of seven studies were included. Patients included ranged from 40 to 41471, and frailty prevalence ranged from 24 to 53%. There was considerable heterogeneity in frailty assessment. Three studies reported higher mortality in frail patients. Frailty was also associated with recurring vascular access failure, higher risk of non-maturation and access thrombosis in included studies. Higher perioperative complications in frail patients were also reported. CONCLUSION: Frailty is associated with adverse outcomes of vascular access in dialysis patients, including thrombosis, longer time to functional use of access, and reintervention. Frail patients also have higher mortality after vascular access construction when compared to non-frail patients. Frailty assessment might be a valuable tool in shared decision-making regarding vascular access in dialysis population.